2016
DOI: 10.1002/adma.201605056
|View full text |Cite
|
Sign up to set email alerts
|

Melt‐Processing of Complementary Semiconducting Polymer Blends for High Performance Organic Transistors

Abstract: Melt-processing of complementary semiconducting polymer blends provides an average charge carrier mobility of 0.4 cm V s and current on/off ratios higher than 10 , a record performance for melt-processed organic field-effect transistors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
109
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 37 publications
2
109
0
Order By: Relevance
“…In 2017, Mei et al [42] reported a novel strategy to make meltprocessing complementary semiconducting polymer blends (c-SPBs) without conventional solution-processing methods. c-SPB was a healable semiconducting polymer that consisted of a matrix polymer with conjugation-break spacers along the polymer backbone and a fully conjugated polymer as tie chain polymer.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Mei et al [42] reported a novel strategy to make meltprocessing complementary semiconducting polymer blends (c-SPBs) without conventional solution-processing methods. c-SPB was a healable semiconducting polymer that consisted of a matrix polymer with conjugation-break spacers along the polymer backbone and a fully conjugated polymer as tie chain polymer.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50] It is believed that API engineering could significantly improve the overall device performance of OFETs and move OFETs towards practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first time for the mobility of such blend exceeds 1 cm 2 V −1 s −1 . [41,42] We also proved that zone annealing could be integrated with melt processing to realize a solvent-free process of polymer thin films for transistor devices. The mobility of each device based on c-SPB material processed from melt processing increased after zone annealing, and the highest mobility (0.54 cm 2 V −1 s −1 ) attained has been a record performance for melt-processed organic field-effect transistors.…”
mentioning
confidence: 99%
“…DPP-C0 and DPP-C5 were prepared following the reported procedure. [20] The weight ratio of blend we investigated in this work was 5:95 (W DPP-C0 :W DPP-C5 = 5:95), exhibiting a melting point of 139.3 °C, [42] thus, the blend could melt at a low temperature. Dichlorobenzene solutions of DPP-C0 (3.3 mg mL −1 ) and DPP-C5 (10 mg mL −1 ) were used as the original solutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation